Spatial Variation of the Demographic Characteristics of Rural Women in Saqlawiyah District in 2022 - Al-Mohammadi, Buthaina Rahim Shawkat; Al-Sharifi, Sahar Abdul Hadi Hussein (Journal of Ecohumanism, 2024)
The spatial variation in the demographic characteristics of rural women in the Saqlawiyah district for this research is an essential step for planning and social and economic development processes and for determining human needs and requirements in the present and future. Population characteristics include demographic, social, and financial data in a specific period, and studying them is of great importance in clarifying the demographic features that characterize women, determining the geographical components and the extent of their impact on the demographic characteristics of rural women, identifying the spatial and temporal distribution of the size and rate of population growth of rural women, recognizing the problems they suffer from, and finding solutions. In order to achieve these goals, attention must be given to girls’ education by building more schools in rural areas, as well as paying attention to their health, providing care and watchfulness for the mother, achieving justice and equality in the distribution of job opportunities and wages, protecting women from domestic violence, and imposing strict laws against anyone does this to a woman.